Mesothelioma in Situ of the Spermatic Cord Arising from a Patent Processus Vaginalis: A Case Report - Kobayashi, Yasuyuki; Yasuhara, Yumiko; Arai, Hiroki; Honda, Masahito; Hiramatsu, Masataka; Goya, Sho (Urology Journal, 2020)
Mesothelioma is an aggressive tumor originating from mesothelial cells. Mesothelioma of the spermatic cord is a very rare disease, and the most common presentation of this disease is that of aggressive mesothelioma with no description of mesothelioma in situ. We report an extremely rare case of mesothelioma in situ of the spermatic cord arising from a patent processus vaginalis. To our best knowledge, this is the first report of this finding. The identification of a patent processus vaginalis and investigation of single-layered atypical mesothelial cells led to the final diagnosis.